Public corporations in Africa: A continental survey on stock exchanges and capital markets performance - Dirk Schiereck; Andreas Freytag; Maximilian Grimm; Wolfgang H. Bretschneider (Friedrich Schiller University Jena, 2018)
While mature capital markets in Western economies suffer from a significant drop in listed companies for two decades, the number of listings at stock exchanges on the African continent is increasing and the importance of stock exchanges for equity issues is growing. This not only raises questions about the future of stock exchanges as platforms to raise equity in different countries (Doidge et al., 2017; Kahle and Stulz, 2017). It also sheds light on the growing importance of African markets for Western actors. The capital markets in Africa, however, are dominated by a very few large stock exchanges while most of the markets are small and underdeveloped based on international standards. The paper serves the purpose of identifying the potential of African stock markets.
Keywords: G10; G23; 330; African capital markets; stock exchange; performance; listings